Reversible structural transformation and redox properties of Cr-loaded iron oxide dendrites studied by in situ XANES spectroscopy. Issue 48 (8th December 2020) - Matsui, Hirosuke; Ishiguro, Nozomu; Suzuki, Youya; Wakamatsu, Kouhei; Yamada, Chiharu; Sato, Kanako; Maejima, Naoyuki; Uruga, Tomoya; Tada, Mizuki
Abstract : Cr-Loaded iron oxide with a dendritic crystalline structure was synthesized and the reversible crystalline phase transition during redox cycling of the iron oxide was investigated. Abstract : Cr-Loaded iron oxide with a dendritic crystalline structure was synthesized and the reversible crystalline phase transition during redox cycling of the iron oxide was investigated. X-ray diffraction and transmission electron microscopy analyses revealed that Cr was well dispersed and loaded in the iron oxide dendrite crystals, whose lattice constant was dependent on the Cr loading. Temperature-programmed oxidation and reduction experiments revealed the reversible redox properties of the Cr-loaded iron oxide dendrites, whose redox temperature was found to be lower than that of Cr-free iron oxide dendrites. In situ Fe K-edge and Cr K-edge X-ray absorption near-edge structure (XANES) analysis indicated that Cr loading extended the redox reaction window for conversion between Fe3 O4 and γ-Fe2 O3 owing to compressive lattice strain in the iron oxide spinel structures.